Blood count reference intervals for the Brazilian adult population: National Health Survey - Ana Carolina Micheletti Gomide Nogueira de Sá; Nydia Strachman Bacal; Crizian Saar Gomes; Tércia Moreira Ribeiro da Silva; Renata Patrícia Fonseca Gonçalves; Deborah Carvalho Malta (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2023)
ABSTRACT Objective: To estimate the reference intervals (RIs) of complete blood count parameters in the Brazilian adult population. Methods: Cross-sectional study, with data from the National Health Survey (Pesquisa Nacional de Saúde - PNS), between 2014-2015. The final sample consisted of 2,803 adults. To establish the RIs, exclusion criteria were applied, outliers were removed and partitions were made by gender, age, and race/skin color. The non-parametric method was adopted. Differences were assessed using the Mann Whitney and Kruskal Wallis tests (p≤0.05). Results: There were statistically significant differences for the following hematological parameters based on gender, red blood cells, hemoglobin, hematocrit, MCH, MCHC, eosinophils and absolute monocytes, neutrophils and platelets (p≤0.05). When analyzed by age, the RIs were statistically different in females for hematocrit, MCV, white blood cells and RDW and in males for red blood cells, white blood cells, eosinophils, mean platelet volume, MCV, RDW, and MCH (p≤0.05). For race/color, there were differences in the RIs for parameters of hemoglobin, MCH, MCHC, white blood cells and mean platelet volume, neutrophils and absolute eosinophils (p≤0.05). Conclusion: The differences found in the RIs of some in blood count parameters in Brazilian adults reaffirm the importance of having their own laboratory reference standards. The results can support a more accurate interpretation of tests, adequate identification and disease prevention in Brazil.